PERAN MOTIVASI DALAM MENINGKATKAN PRODUKTIVITAS UMKM DI ERA EKONOMI DIGITAL - Anriani Ritonga, Mei; Ruslita Batubara, Aisyah Norma; Lubis, M. Syahrozi; Hayati, Fitri (LP2M Universitas Bina Bangsa, 2025)
This study aims to examine the role of motivation, both intrinsic and extrinsic motivation in increasing the productivity of Micro, Small and Medium Enterprises (UMKM) in the digital era. This study also focuses on identifying the types of motivation that have the most influence on the success of UMKM digital transformation. The method used in this study is descriptive with a qualitative approach based on secondary data taken from various relevant journals. The results of this study indicate that intrinsic motivation, such as the desire to develop, learn and innovate, and extrinsic motivation, such as government support, financial incentives and awards, significantly increase UMKM productivity.